1961
DOI: 10.1139/v61-162
|View full text |Cite
|
Sign up to set email alerts
|

Π-Bonding IN INORGANIC COMPOUNDS: III. A MAGNETOCHEMICAL STUDY OF HEXAHALOOSMATES AND HEXACHLORORHENATE

Abstract: The anonialously small magnetic niornents of o s n~i~~n~ ( l V ) and rhenium(1V) in their hexahalo complexes are investigated by measurement of the magnetic susceptibilities of the mixed crystal systems, 1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1961
1961
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Hexahalorhenate(IV) salts are among the first examples of magnetic studies on rhenium(IV) complexes. The investigations of the magnetic properties of different ionic salts containing the [ReX 6 ] 2- anion (X = F, Cl, Br, or I) which were carried out by several research groups in the temperature range 80−300 K suggested the occurrence of large antiferromagnetic interactions between the paramagnetic Re(IV) centers (three unpaired electrons on each rhenium atom). Figgis et al pointed out that the magnetic exchange in these systems depends on the tendency of the metal electrons to be transferred to the X ligand and on the X···X separation between the anions in the lattice. In this sense, they found that the antiferromagnetic interaction on different [ReCl 6 ] 2- salts can be related with the size of the cation, and that the magnitude of the magnetic coupling for the potassium and cesium salts of [ReX 6 ] 2- increases in the order F < Cl < Br < I, even when different crystal structures of the ionic salts are involved.…”
Section: Introductionmentioning
confidence: 99%
“…Hexahalorhenate(IV) salts are among the first examples of magnetic studies on rhenium(IV) complexes. The investigations of the magnetic properties of different ionic salts containing the [ReX 6 ] 2- anion (X = F, Cl, Br, or I) which were carried out by several research groups in the temperature range 80−300 K suggested the occurrence of large antiferromagnetic interactions between the paramagnetic Re(IV) centers (three unpaired electrons on each rhenium atom). Figgis et al pointed out that the magnetic exchange in these systems depends on the tendency of the metal electrons to be transferred to the X ligand and on the X···X separation between the anions in the lattice. In this sense, they found that the antiferromagnetic interaction on different [ReCl 6 ] 2- salts can be related with the size of the cation, and that the magnitude of the magnetic coupling for the potassium and cesium salts of [ReX 6 ] 2- increases in the order F < Cl < Br < I, even when different crystal structures of the ionic salts are involved.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous publication (3) it was shown that there is extellsive superexchange ill IC20sC16, Ii20sBrG, and IC2ReC1G. 'rl~is apparently operates through d,-/I, bonding orbitals which encompass the metal atom and its ligands a n d , as well, p,-p, overlap between the ligands of the neighboring complex groups (4).…”
mentioning
confidence: 99%
“…They were determined on a modified Chevenard thermobalance in a nitrogen atmosphere as described elsewhere. 8 In a separate run a sample of Zn2(IDP)(CgHgPOg)2 was taken to constant weight at 350°. Anal.…”
Section: Methodsmentioning
confidence: 99%